LONG-TERM FOLLOW-UP ON A RARE CASE OF PERIOPERATIVE POSTERIOR ISCHEMIC OPTIC NEUROPATHY: FINDING HOPE IN THE DARKNESS: Poster Presentation - Case Report - Resident - Affannul Hakim; Lukisiari Agustini; Gatot Suhartono (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Perioperative posterior ischemic optic neuropathy (PION) following maxillectomy is a rare and devastating condition that leads to permanent vision loss in most reported cases. This case report offers a different perspective through long-term follow-up, providing valuable insights into the prognosis and potential treatments for PION. Case Illustration : Following a left maxillectomy for ameloblastoma, a 28-year-old female experienced sudden vision loss in her left eye. The visual acuity was 5/60, and an altitudinal inferior visual field defect with a superior extension was present. Ishihara's color vision examination revealed 15/38. The patient was diagnosed with perioperative PION and treated with neurotropic and folic acid. After 16 months, optic atrophy was observed. However, there are complete recovery in visual acuity to 5/5 and Ishihara score to 38/38, along with a significant improvement in the visual field defect. Discussion : The current management of perioperative PION is focused on prevention, because once vision loss occurs, it is usually severe and irreversible. In our case, the patient exhibited a favorable outcome after a long follow-up period, suggesting that there is still potential for improvement in PION patients. The finding is consistent with previous study, which reported that a small percentage of patients may still experience improved vision during follow-up. The role of neurotropics in improving patient outcomes is further supported by in vitro studies that demonstrate early neurotropic treatment significantly prevents loss of retinal ganglion cells in PION. Conclusion : Visual improvement is still possible in perioperative PION and early neurotropic administration may be considered in therapy